Antioxidant activity of dorzolamide/timolol fixed combination in neuroprotective therapy in glaucoma - N. I. Kurysheva; O. A. Azizova; A. P. Piryazev (Oftalʹmologiâ, 2014)
Purpose: to study the antioxidant activity of carbonic anhydrase inhibitors and timolol fixed combinations and to compare it with other fixed combinations.Methods: Antioxidant activity (AOA) of dorzolamide/timolol (Cosopt), dorzolamide/timolol (Dorzopt Plus), latanoprost/timolol, brimonidine/timolol, travoprost/timolol and bimatoprost/timolol fixed combinations was measured in vitro using the model of oxida- tive hemolysis.Results: Dorzolamide/timolol (Cosopt) AOA was higher than that of other fixed combinations and increased with the quantity of the drugs added to the model system: 40%, 52% and 75% in 30 μl, 60 μl and 90 μl respectively.Conclusion: these findings suggest that dorzolamide/timolol fixed combination has potential advantages over the other fixed combinations due to its high antioxidant activity and might be used as the neuroptotective agent for glaucoma treatment.